Efficacy and safety of live varicella zoster vaccine in diabetes: a randomized, double‐blind, placebo‐controlled trial. Issue 8 (29th December 2015) - Hata, A.; Inoue, F.; Hamamoto, Y.; Yamasaki, M.; Fujikawa, J.; Kawahara, H.; Kawasaki, Y.; Honjo, S.; Koshiyama, H.; Moriishi, E.; Mori, Y.; Ohkubo, T.
Abstract: Aims: To elucidate varicella zoster virus (VZV)‐specific cell‐mediated immunity and humoral immunogenicity against live attenuated Oka varicella zoster vaccine concurrently vaccinated with 23‐valent pneumococcal polysaccharide vaccine (PPSV23) in elderly people with diabetes mellitus. Methods: This double‐blind randomized controlled single‐centre study of 60–70‐year‐old people with diabetes compared immunity and safety profiles 3 months after one dose of varicella zoster vaccine or placebo. PPSV23 was immunized simultaneously. Primary analysis evaluated cell‐mediated immunity using the VZV skin test. Secondary analyses were a VZV interferon–γ enzyme‐linked immunospot (ELISPOT) assay and immunoadherence haemagglutination test. Adverse experiences were recorded using diary questionnaires. Results: By intent‐to‐treat analysis, 27 participants with diabetes who had been administered the vaccine were compared with 27 participants who were given a placebo. Changes in skin test scores were 0.41 ± 0.80 and 0.11 ± 0.93 ( P = 0.2155), and geometric mean fold rises of the ELISPOT counts were 1.2 [95% confidence interval (CI) 0.2, 7.9] and 1.2 (95% CI 0.2, 7.3) ( P = 0.989) in the vaccine and placebo groups, respectively. The geometric mean titre did not increase 3 months after vaccination in either group. No vaccination‐related severe adverse experience was reported and no participant developed herpes zoster. Discussion: Our previous results demonstrated that varicella zoster vaccine safely enhanced VZV‐specific immunity in elderly people with or without diabetes. The results of this study showed that varicella zoster vaccine can be used safely, but it cannot boost virus‐specific immunity in elderly people with diabetes when administered with concurrent PPSV23. Alternative strategies are needed to prevent VZV‐associated diseases in this population. What's new?: This first randomized, double‐blind placebo‐controlled study evaluated cell‐mediated immunity (CMI) to live varicella zoster vaccine in 60‐70‐year‐old patients with diabetes simultaneously immunized with pneumococcal polysaccharide vaccine (PPSV23). Primary outcomes were CMI‐assessed by varicella zoster virus (VZV) skin test. Secondary outcomes were VZV interferon‐gamma ELISPOT assay, immunoadherence hemagglutination test and adverse experiences. By intent‐to‐treat analysis, the vaccine was used safely but did not boost VZV‐specific immunity in elderly patients with diabetes compared to placebo. Our earlier report described that live varicella zoster vaccine enhanced CMI to VZV in elderly patients with or without diabetes. Concurrent PPSV23 administration might affect immune response.